Clean Water Crisis and Climate Change: Study of Clean Water Resource Management in Gunung Kidul - Angga Misbahuddin (Jurnal Studi Sosial dan Politik, 2021)
Gunung Kidul is one of the areas in the Special Region of Yogyakarta Province which is always hit by a clean water crisis. In fact, clean water is one of the most important human needs that must be protected by its resources. The higher amount of consumption has made many regions experience an air crisis, one of which is Gunung Kidul. In fact, there are effects of climate change that lead to the quantity and quality of water in Gunung Kidul. Therefore, this study aims to explain the policy phenomenon carried out by the Gunung Kidul Government in air management by using a type of literature study research where the authors collect various sources from journals and other literature on climate change, management policies, and the water crisis. By using the theory of implementing public policy and the concept of integrated water resource management, the results show that Gunung Kidul Regency is experiencing climate change, as seen from an increase in average air temperature, inconsistent rainfall, and rising seawater. Climate change that occurs indirectly affects the quantity and quality of existing resources, causing a clean water crisis in various areas in Gunung Kidul Regency. In response to this, the government has not implemented the air resources management policy optimally, this is based on the incomplete air distribution, high PDAM water rates, minimal utilization of water resources, and water resources conservation activities that have not been optimal. Therefore, some appropriate steps that can be taken are, first, making efforts to utilize air resources other than air resources. Second, expanding the distribution of air pipelines from PDAM along with affordable payment rates. Third, maintaining the quality of resources in drought-prone areas through mining activities.